1 : Just global socioecological transformations: It takes a worldview change to change the world? - Ramcilovic-Suominen, Sabaheta (Routledge, 2025)
The chapter introduces the 14 contributions of this edited volume, as well as the aims and scope of the book, and the book’s contributions to socioecological transformations literature. The book responds to several trends identified in transformations literature, including (i) apolitical and ahistorical framing of transformations, which waters down the concept with intended or unintended benefit of the status quo, and (ii) the tendency to overemphasize the structures and structural causes of socioecological violence and destruction, while overlooking their ontological bases of those very structures and the associated structural violence. The book also responds to and challenges the related trend of (iii) portraying social movements and activism as the only viable responses to socioecological violence and strategies for transformations. In the light of these trends, the book emphasizes the deeper roots of the current socioecological violence, namely the materialist-dualist ontologies as the basis for the colonial-racial-capitalist systems and the associated structural violence. It broadens the spectrum of viable means and responses for transformations to include those that question and seek to unlearn and undo the ontological foundations of the colonial-racial-capitalist systems and the associated socioecological violence and destruction, and that do so through a wider range of means, including contemplation, practice of deep interconnectedness, and inner personal and collective changes. Such ontological causes and responses are proposed as complementary, rather than supplementary, to those that focus on structures and direct action through social movements. The chapter dives into the diverse ontological positions, from materialist and dualist to idealist, pluralist, relational, and nondualist ontologies. It outlines the key concepts engaged within the book, including deep relationality, potentiality, entanglement, radical intraconnectedness, ecological self, ecologies of mind, worlding, ontological transformations, care as politics and care as ethics, shadow forests, ecological livelihoods, epistemic (in)justice, epistemicide, scholasticide, and degrowth tourism. It concludes with some omissions and editor’s reflection on her positionality.
Keywords: political ecology; social movements